Visit Albert and Rose Watkins 207 Geneva Avenue, Huntington Beach, CA - Watkins, Howard::::::::: (1981)
Adam Watkins in school chair with Albert Watkins, Rose Watkins, Ann Finer, Christine Watkins, Howard Watkins